Chemical Differentiation by Mineralogical Buffering in Crustal Hot Zones. (22nd June 2022) - Blundy, Jon
Abstract: Chemical diversity in convergent margin magmas is a product of igneous differentiation in crustal hot zones, vertically extensive regions characterised by a low-volume (<20%) mobile melt phase dispersed in a crystal-rich mush. Chemical reaction between buoyant, percolating melts and the surrounding mush leads to chemical buffering by the local mineral assemblage. Where this assemblage has low thermodynamic variance (e.g. six mineral phases plus melt and H2 O-CO2 fluid) the resultant multiply saturated melts will show limited chemical variability. Plutonic xenoliths from many volcanic arcs, as well as exhumed arc crustal sections, testify to the ubiquity of low-variance, broadly gabbroic, mineral assemblages. Here I use the concept of multiple saturation to explore the chemical consequences of percolative reactive melt flow in crustal hot zones using data from published experimental studies on a wide variety of different starting materials. I show that the common, low-variance hornblende gabbronorite assemblage clinopyroxene-hornblende-orthopyroxene-magnetite-plagioclase-ilmenite (CHOMPI) coexists with fluid-saturated melt over a wide range of pressure (1–10 kb) temperature (800–1050 °C) and fluid composition (molar fraction H2 O, X H2 O, of 1.0 to 0.3). The CHOMPI stability field is bounded by the following: the appearance of garnet at high pressure, the hydrous haplogranite granite liquidus at low temperature, and amphibole breakdown at high temperature and low pressure. CHOMPI melts cover a wide compositional range (54–74 wt% SiO2 ; 4.4–0.1 wt% MgO) that can be parameterised in terms of five independent variables: pressure, temperature, f O2, molar CO2 /H2 O in the fluid and melt K2 O content. The compositional diversity and broad stability field of CHOMPI-saturated melts make them extremely common in the rock record. Melt composition parameterisations can be inverted to recover pressure (±1.3 kb), temperature (±16 °C) and fluid molar CO2 /H2 O (±0.43) of CHOMPI-saturated melts. If a natural magma composition can be shown to lie on or close to the CHOMPI saturation surface then the conditions under which that melt was last in equilibrium with this mineral assemblage can be established. I apply this method of magma source thermobarometry and hygrometry to the most recent eruptions from 15 Cascades arc volcanic centres. Calculated pressures range from 1.3 to 5.8 kb (5–21 km depth) with significant along-arc variation. Temperatures correlate with pressure and match independent estimates of eruption temperatures from mineral thermometry with the exception of two eruptions where significant (≤10°C) cooling occurred during pre-eruptive magma storage. Fluid X H2 O is in the range 0.47–0.92 and inversely correlates with pressure. Mineralogical buffering of melt chemistry in hot zones is proposed as an important mechanism of chemical differentiation in volcanic arcs. Mineralogical buffering can operate at the low-melt fractions observed in geophysical surveys of arc crust, providing an alternative to traditional concepts of assimilation-fractional crystallisation and liquid lines of descent that operate most effectively in melt-rich systems.